The accuracy value of the dentist’s clinical diagnosis in oral lesions performed on biopsy - Anadza, Galih Fata; Syamsudin, Endang; Yuza, Abel Tasman (Padjadjaran Journal of Dentistry, 2013)
Introduction: The diagnosis of a pathological disorder can be made in various stages, namely history taking, clinical examination and supporting examination. Clinical diagnosis is a diagnosis obtained from anamnesis and the results of clinical examination. Histopathological diagnosis is a diagnosis obtained from a microscopic examination of tissue. Clinical diagnosis and histopathological examination results may differ. The aim of the study was to obtain the accuracy value of the dentist’s clinical diagnosis by calculating the number of differences between the clinical diagnosis and the results of the histopathological examination of patients who were biopsied in the Department of Oral Surgery of General Hospital Dr. Hasan Sadikin Bandung. Methods: A retrospective descriptive study of cases of pathological abnormalities biopsied in the Department of Oral and Maxillofacial Surgery of General Hospital Dr Hasan Sadikin Bandung. The total number of study samples was 109 medical records of patients with biopsy. Results: The accuracy value of the clinical diagnosis of dentists was 76%, where the difference between the clinical diagnosis and the histopathological examination was 24%. The most common type of disorder with the greatest difference in diagnosis is ameloblastoma followed by papilloma and mucocele. Conclusion: The accuracy value of the clinical diagnosis of dentists in oral lesions performed biopsy is 76%.